2015
DOI: 10.1007/s11046-015-9890-5
|View full text |Cite
|
Sign up to set email alerts
|

Chaetomium globosum Cutaneous Fungal Infection Confirmed by Molecular Identification: A Case Report from Malaysia

Abstract: An 11-year-old girl presented with multiple blisters on her the right foot complicated with cellulitis. The conventional and molecular identification were performed on the culture. The internal transcribed spacer (ITS) region in rRNA gene of the isolate was amplified by PCR. The sequence of the amplified ITS region matched 99 % with that of Chaetomium globosum in the GenBank. This is the first report describing C. globosum causing cutaneous infection in Malaysia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…In the present study, the highest resistance rate (72.5%) was to ITZ, both consistent ( 2 , 21 , 22 ) and inconsistent ( 24 , 27 ) with the findings of previous studies. The findings on resistance to ITZ differ slightly from those reported in the U.S., Canada, Europe, and Latin America ( 2 , 21 , 22 ). In the latter regions, C. glabrata was reported to be most resistant to ITZ, followed by C. krusei and C. tropicalis .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, the highest resistance rate (72.5%) was to ITZ, both consistent ( 2 , 21 , 22 ) and inconsistent ( 24 , 27 ) with the findings of previous studies. The findings on resistance to ITZ differ slightly from those reported in the U.S., Canada, Europe, and Latin America ( 2 , 21 , 22 ). In the latter regions, C. glabrata was reported to be most resistant to ITZ, followed by C. krusei and C. tropicalis .…”
Section: Discussionsupporting
confidence: 90%
“…Among pathogenic fungi, Candida species are most common cause of candidemia infections, with high mortality rates, and the incidence of candidemia infections has significantly increased in recent decades ( 1 , 2 ). Although C. albicans is the most frequently detected fungal species in this type of infection, non- C. albicans species ( C. glabrata , C. tropicalis , C. parapsilosis , and C. krusei ) have been increasingly detected, particularly in high-risk populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA extractions, amplifications by polymerase chain reaction (PCR), PCR product purification and sequencing methods were performed as previously described [ 12 ]. The internal transcribed spacer (ITS) and the D1/D2 domain of the large subunit (LSU) in rRNA gene regions were amplified using universal primers ITS5/ITS4 [ 13 ] and NL1/NL4 [ 14 ].…”
Section: Molecular Identificationmentioning
confidence: 99%
“…They are known to be causative agent for emerging fungal infections in human being. The spectrum of disease include onychomycosis, superficial and deep mycoses, brain abscess, sinusitis and pneumonia . Here, we report Chaetomium globosum as a cause of invasive pulmonary infection in a patient with Wegener's granulomatosis and review all the Chaetomium infections reported till date.…”
Section: Introductionmentioning
confidence: 99%